The TOR Signaling Pathway in Spatial and Temporal Control of Cell Size and Growth - Gonzalez, Suam; Rallis, Charalampos (Frontiers in Cell and Developmental Biology, 2017)
Cell size is amenable by genetic and environmental factors. The highly conserved nutrient-responsive Target of Rapamycin (TOR) signaling pathway regulates cellular metabolic status and growth in response to numerous inputs. Timing and duration of TOR pathway activity is pivotal for both cell mass built up as well as cell cycle progression and is controlled and fine-tuned by the abundance and quality of nutrients, hormonal signals, growth factors, stress and oxygen. TOR kinases function within two functionally and structurally discrete multiprotein complexes, TORC1 and TORC2, that are implicated in temporal and spatial control of cell size and growth respectively; however, recent data indicate that such functional distinctions are much more complex. Here, we briefly review roles of the two complexes in cellular growth and cytoarchitecture in various experimental model systems.